Short and efficient synthetic strategy for the total syntheses of (S)-(+)- and (R)-(-)-Plakolide A - Mohapatra, Debendra K.; Pramanik, Chintnoy; Chorghade, Mukund S.; Gurjar, Mukund K. (European Journal of Organic Chemistry, 2007)
Concise and efficient total syntheses of anticancer agents (S)(+)-Plakolide A and (R)-(-)-Plakolide A were accomplished in eight steps and an overall yield of 39 % starting from geraniol. The key steps in our strategy are Sharpless asymmetric epoxidation, double elimination, and Stille coupling reactions.
Keywords: Cross-coupling; epoxidation; inhibitors; olefination